THE RELATIONSHIP BETWEEN HIGH-PERFORMANCE SPORTS AND ANTERIOR CRUCIATE LIGAMENT (ACL) INJURIES: A SYSTEMATIC REVIEW (International Seven Journal of Health Research, 2025)
This article investigates the relationship between high-performance sports and Anterior Cruciate Ligament (ACL) injuries. The high incidence of these injuries, especially in sports involving rapid changes of direction, highlights the need to understand their mechanisms, risk factors, and prevention strategies. The research was conducted through an integrative literature review, with the aim of understanding the main risk factors, clinical consequences, and prevention strategies related to ACL injuries. Articles published between 2020 and 2025, selected from the PubMed and Virtual Health Library (VHL) databases, were analyzed. After applying inclusion and exclusion criteria, eight relevant studies were examined. The results indicate that most ACL injuries occur without direct contact, being attributed to biomechanical and neurocognitive factors, such as incorrect landings, inadequate hip flexion, and cognitive distractions during the game. Specific cases reveal that, in badminton, the scissor jump is frequently associated with the injury; In rugby, 75% of ruptures occur in the first 40 minutes of play; and in the WNBA, the average time to return from injury is 375 days. Furthermore, genetic studies suggest the possible influence of loci such as COL22A1 on susceptibility to ruptures. ACL injuries have a significant impact on athletes' sports careers and quality of life, resulting in prolonged absences and a high risk of recurrence. In view of this, the importance of adopting prevention programs focused on muscle strengthening, neuromotor control and movement reeducation is reinforced, as a way of preserving the performance and health of high-performance athletes.